2022
DOI: 10.1093/nar/gkac070
|View full text |Cite|
|
Sign up to set email alerts
|

High mobility group AT-hook 1 (HMGA1) is an important positive regulator of hepatitis B virus (HBV) that is reciprocally upregulated by HBV X protein

Abstract: Chronic infection with hepatitis B virus (HBV) is associated with liver cirrhosis and hepatocellular carcinoma. Upon infection of hepatocytes, HBV covalently closed circular DNA (cccDNA) exists as histone-bound mini-chromosome, subjected to transcriptional regulation similar to chromosomal DNA. Here we identify high mobility group AT-hook 1 (HMGA1) protein as a positive regulator of HBV transcription that binds to a conserved ATTGG site within enhancer II/core promoter (EII/Cp) and recruits transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…According to the study by Shen et al, HMGA1 protein could positively regulate HBV transcription via recruiting transcription factors forkhead box O3alpha (FOXO3α) and peroxisome proliferator-activated receptor-γ coactivator-1α (PGC1α). On the other hand, HMGA1-targeted treatment facilitates HBV clearance ( Shen et al, 2022 ). Similarly, Andreozzi et al observed monotonically increased HMGA1 expression in tissues from normal liver to cirrhotic transformation, to primary HCC and to disease metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Shen et al, HMGA1 protein could positively regulate HBV transcription via recruiting transcription factors forkhead box O3alpha (FOXO3α) and peroxisome proliferator-activated receptor-γ coactivator-1α (PGC1α). On the other hand, HMGA1-targeted treatment facilitates HBV clearance ( Shen et al, 2022 ). Similarly, Andreozzi et al observed monotonically increased HMGA1 expression in tissues from normal liver to cirrhotic transformation, to primary HCC and to disease metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other end of the functional spectrum, many VIPs do not have any immune function and are in fact proviral factors that assist viruses when the latter hijack their molecular functions to complete multiple steps of their replication cycle (Table S1). For example, viruses subvert host transcription regulators to activate the expression of their own viral genes during infection (Chau et al, 2008; Scoggin et al, 2001; Shen et al, 2022). We predict that immune antiviral and non-immune proviral VIPs should have experienced different patterns of protein stability evolution.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study described the extraction of HBV cccDNA [50][51][52]. Cells were lysed in lysis buffer containing 50 mM Tris-HCl, pH 7.4, 1 mM EDTA, and 1% NP-40 supplemented with proteinase inhibitor cocktail (Topscience, China) for 10 min.…”
Section: Hbv Cccdna Quantitationmentioning
confidence: 99%